(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines aspects of the terminological dictionary related to the field of mining, which differ from dictionaries related to the language field, as well as some specific features of the terminological dictionary. The literary relationship of linguistic and special vocabulary, terminological units with “normative” elements and the features of terms in the context of mining are studied.